2023
DOI: 10.7759/cureus.36597
|View full text |Cite
|
Sign up to set email alerts
|

Is Systemic Inflammatory Response Index (SIRI) a Reliable Tool for Prognosis of Gastric Cancer Patients Without Neoadjuvant Therapy?

Abstract: Background: The systemic inflammatory response index (SIRI), which depends on peripheral neutrophil, monocyte, and lymphocyte count, was found as an effective prognostic indicator for various malignancies. This study aims to investigate the predictive value of preoperative SIRI in the prognosis of gastric cancer patients without neoadjuvant therapy.Methods: The patients who underwent gastric cancer surgery in Marmara University Hospital's General Surgery Department between 2019 and 2021 were analyzed retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…SIRI was calculated based on the counts of neutrophils, monocytes, and lymphocytes in peripheral blood, accurately reflecting the tumor’s inflammatory status. Notably, it demonstrated a superior ability to assess the prognosis of gastric cancer patients compared to other traditional inflammatory indicators ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…SIRI was calculated based on the counts of neutrophils, monocytes, and lymphocytes in peripheral blood, accurately reflecting the tumor’s inflammatory status. Notably, it demonstrated a superior ability to assess the prognosis of gastric cancer patients compared to other traditional inflammatory indicators ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…in 2016 for pancreatic cancer prognosis [ 11 ]. Recent studies have reported the prognostic effect of SIRI for various cancers, including nasopharyngeal carcinoma (NPC) [ 12 ], colorectal [ 13 ], ovarian [ 14 ], gastric [ 15 ], and bladder cancers [ 16 ]. Many previous studies have explored the significance of the SIRI in predicting BC prognosis, but no consistent findings have been obtained [ 17–24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The systemic inflammation response index (SIRI) is a novel hematologic parameter that was first proposed in 2016 ( 12 ) and is determined using the following formula: SIRI = (neutrophil × monocyte)/lymphocyte count. SIRI has been widely suggested to exhibit a significant and powerful value in predicting solid tumors such as bladder cancer ( 13 ), non-small cell lung cancer (NSCLC) ( 14 ), gastric cancer ( 15 ), breast cancer ( 16 ), and ovarian cancer ( 17 ). The impact of the SIRI on predicting HCC prognosis has also been explored; however, no consistent findings have been found ( 18 27 ).…”
Section: Introductionmentioning
confidence: 99%